Nurses' Experiences as Care Providers for Syrian Refugees With Noncommunicable Diseases: A Qualitative Study. (January 2023) - Kuru Alici, Nilgun; Öztürk Çopur, Ebru
Introduction: Noncommunicable diseases (NCDs) are the leading cause of disability and death in the world. In Syria, the incidence of NCDs in refugees is 45%. Cardiovascular diseases, cancers, chronic respiratory diseases, diabetes, and other NCDs are the most common causes of morbidity in Syria. Nurses have challenges caring for Syrian refugees with NCDs. The purpose of the study was to explore nurses' experiences of caring for Syrian refugees with NCDs in Turkey. Methodology: A phenomenology design was used. Inclusion criteria were nurses working experience of more than 1 year, caring for Syrian refugees with NCDs, and willingness and ability to participate in an individual interview. The participants were 20 nurses who worked with Syrian refugees at a public hospital in Kilis Province the border with Syria . Data were collected using semistructured interviews and analyzed by the thematic analysis method of Braun and Clarke. Results: Three major themes and six subthemes were identified. Major themes included the communication experience, cultural differences, and Syrian refugees' lack of knowledge about NCDs. Discussion: The results provide insight related to nursing care in Turkey for Syrian refugees with NCDs. The study revealed that nurses encountered challenges when caring for Syrian refugees with NCDs. Culturally competent assessment and interventions for refugees with NCDs should be encouraged considering these three themes.